White men challenging racism 35 personal stories - Thompson, Cooper 1950-; Schaefer, Emmett Robert 1947-; Brod, Harry 1951-; Loewen, James W. 1942-2021 (Duke University Press, 2012)
Introduction -- Movement elders -- The Next Generation -- Appendix : interview questions and editing guidelines